PROSES KREATIF MUA (MAKE UP ARTIST) PEKALONGAN DALAM MENGHADAPI TANTANGAN DI ERA DIGITAL - Indrasmara, Atmanurvita Prameswari; Jazuli, Muhammad; Syarif, Muh. Ibnan (Institut Seni Indoensia Surakarta, 2024)
ABSTRACTThe arts industry is an industry that requires talent, creativity and innovation. Bridal make-up is an industry that must be equipped with these three elements. This is interesting to research because creativity must compete in the midst of the digital era, where a MUA (Make Up Artist) must be clever at brainstorming by continuing to be creative and innovative and have an adaptive attitude to adapt to challenges in the digital era in order to maintain its existence. This research aims to determine the creative process of a MUA (Make Up Artist) in Pekalongan and the challenges of a Pekalongan MUA (Make Up Artist) in facing challenges in the digital era. This research is a type of qualitative research. The research method used is the descriptive-analysis method. Data collection was carried out through observation, interviews, literature study and documentation study. The analysis used is data analysis starting from data collection, data reduction, data presentation and drawing conclusions. This writing will begin with a description of (1) The creative process of MUA (Make Up Artist) in Pekalongan, (2) Challenges of MUA (Make Up Artist) facing the digital era.